PENGARUH PEMBERIAN JENIS PAKAN YANG BERBEDA TERHADAP LAJU PERTUMBUHAN BENIH IKAN NILA (Oreochiomis niloticus) DAN KUALITAS AIR DI AKUARIUM PEMELIHARAAN - Vita Yanuar (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
Feeding is closely related to the growth rate of the fish. In order to utilize the natural feed ingredients to reduce operating costs and production, the utilization of kale leaves as a natural food is expected to increase the growth rate in tilapia (Oreochiomis niloticus). The research objective was to determine the significance of the effect of different feeding on the rate of growth of tilapia on the size of 3-5 cm during the maintenance period of 28 days and know the quality of the water that supports the growth rate of tilapia fish. The experimental design used in this study is Complete Random Design (CRD) single factor consisting of 3 treatments 3 repetitions. The treatments used are feeding kale, pellet, and pellet and kale. The results showed that the maintenance media (aquarium) tilapia fish with different feeding treatment no significant effect on the growth of the weight and length of tilapia fish. Water quality on the results of this study are still in the range of eligibility for the growth and development of tilapia fish is to a temperature of 26.5 to 28.5 oC; pH ranges from 6.0 to 7.2; DO 6.7 to 6.67 mg/l; and ammonia 2.96 to 3.77 mg/l.